Clinical and radiographic outcomes of supracondylar humerus fractures treated surgically by pediatric and non-pediatric orthopedic surgeons. (February 2015) - Dodds, Seth D.; Grey, Monique A.; Bohl, Daniel D.; Mahoney, Eamonn M.; DeLuca, Peter A.
Purpose: This study compares clinical and radiographic outcomes of operatively managed pediatric supracondylar humerus fractures between patients treated by pediatric orthopedists (POs) and patients treated by non-pediatric orthopedists (NPOs). Patients and methods: A retrospective cohort study of pediatric patients with surgically managed supracondylar humerus fractures was conducted. For clinical outcomes analyses, 3 months of clinical follow-up were required, resulting in a sample size of 90 patients (33 treated by NPOs, 57 by POs). For radiographic outcomes analyses, 3 months of both clinical and radiographic follow-up were required, resulting in a sample size of 57 patients (23 treated by NPOs, 34 by POs). Results: The rate of inadequate fracture fixation was higher for patients treated by NPOs (43.5 %) than for patients treated by POs (14.7 %; p = 0.030), but rates of clinical complications, malreduction, and postoperative loss of reduction did not differ. Treatment with open reduction was more common for patients treated by NPOs (33.3 %) than for patients treated by POs (3.5 %; p < 0.001). Total operating room time was longer for patients treated by NPOs (110.9 min) than for patients treated by POs (82.9 min; p < 0.001). Conclusions: While patients treated by POs differed from patients treated by NPOs with respect to several intermediate outcomes, including having a lower rate of open reduction and a lower rate of inadequate fracture fixation, there were no differences between POs and NPOs in the rates of the more meaningful and definitive outcomes, including clinical complications, malreduction, and postoperative loss of reduction.